Analisis Pengendalian Kualitas dengan Metode Basic Seven Tools dan Failure Mode And Effect Analysis (FMEA) untuk Meminimasi Kecacatan Produk di PT X - Gatot Basuki; Nataniel Viananda Gusdi; Moch Mahsun (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2025)
Quality serves as a criterion for assessing a product, and consumers use it to gauge their satisfaction with the product based on its actual use. Quality product will ensure customer satisfaction with the results. PT X operates as a sole proprietorship and is involved in the manufacturing and processing of gold to create jewelry using production machinery. One issue with current jewelry manufacturing is that product defects make up 2% of the overall output. Utilizing the Basic Seven Tools method, broken keys were identified as the most frequent type of defect. Meanwhile, the RPN (Risk Priority Number) was calculated using the Failure Mode and Effect Analysis method to rank the risk levels from highest to lowest. The two main defects for broken keys were associated with machine failure.